Relationship between job satisfaction and turnover intention among lecturers in private higher educational institutions in Shandong province in China - Wang, Guixia; Mat Rashid, Abdullah (Human Resource Management Academic Research Society, 2019)
This study explored the relationship between job satisfaction and turnover intention among the lecturers in private Higher Educational Institutions (HEI) in Shandong Province of China. 36-items from Job Satisfaction Survey (JSS) and 6-items from Turnover Intention Scale (TIS-6) were utilized to measure the level of job satisfaction and turnover intention respectively. Through stratified random sampling, 4 private HEI was selected with 231 lecturers involved in this study. The level of job satisfaction was at moderate level (3.05 ± 1.15) and turnover intention was at high level (4.05 ± 0.97). Married lecturers were found to have higher satisfaction with the pay than those single lecturers. Significant negative correlation was found between all the dimensions of job satisfaction and turnover intention. Stepwise linear regression analysis further pin-points the important predictors of turnover intention and they are communication, promotion, pay, co-workers and supervision. This study recommended improvement in the pay level, effective incentive mechanism, fair promotion, solid professional development and rational operating procedure as intervention to curb turnover intention.